BOOK REVIEW: ON WRITING WELL. THE CLASSIC GUIDE TO WRITING NONFICTION - Dieorditsa, Taiana; Voronina, Maryna (Physical and Mathematical Education, 2024)
The book «On writing well» by the American journalist and teacher of writer’s craft W. Zinsser tells about what principles a writer should be guided by and what methods to use to produce a quality nonfiction text.